Taxonomy and stratigraphic distribution of Lotagnostus (Agnostida: Agnostidae) and associated trilobites and conodonts in the Upper Cambrian (Furongian) of Laurentia - Taylor, John F.; Loch, James D.; Repetski, John E. (Zootaxa, 2024)
Two Lotagnostus-dominated faunas from the Windfall Formation at Ninemile Canyon in the Antelope Range of Nevada, USA, are described: an older Lotagnostus nolani Fauna and younger L. rushtoni Fauna. The former is dominated by two morphs of Lotagnostus, one strongly scrobiculate and the other smooth to weakly scrobiculate. Both morphs fall within the broad concept advocated for L. americanus by Peng et al. (2015). The numerous (>1400 sclerites) specimens of Lotaganostus in collections of the L. nolani Fauna confirm that the two morphs do not intergrade and remain distinct throughout ontogeny. Both display multiple traits that distinguish them from the type material of L. americanus, justifying treatment as separate species. Similarly unique, diagnostic features were identified to restore the Asian species L. punctatus and L. asiaticus to full species status, whereas deficiencies in the type material for L. americanus warrant restriction of the name to the holotype. New species described from the Windfall include five agnostoids (Lotagnostus nolani, L. clarki, L. morrisoni, L. rushtoni, and Neoagnostus parki) and one trilobite (Bienvillia eurekensis). Plicatolina nyensis Taylor is reassigned to Mendoparabolina on the form of its pygidium. Conodonts from the Catlin Member of the Windfall Formation and overlying informal Caryocaris shale member of the Goodwin Formation at Ninemile Canyon provide a late Sunwaptan (Eoconodontus Zone) age for the Lotagnostus rushtoni Fauna and assign the entire Caryocaris shale to the early Ordovician Rossodus manitouensis Zone. Combined with published data on trilobite faunas, the conodont faunas confirm strong diachroneity for the top of the Catlin, and a lack of overlap in age between the Caryocaris shale and Bullwhacker Member of the Windfall in ranges to the north and east. Co-occurrence of Lotagnostus nolani and Mendoparabolina nyensis establishes age equivalence of the L. nolani Fauna with the Hedinaspis-Charchaqia (HC) Fauna at the base of the Hales Limestone in the Hot Creek Range, and earlier correlations of the latter with the L. punctatus Zone in Asia are supported. However, isolation of the HC Fauna in starved-basin deposits above a major sequence boundary at the base of the Hales, and ecologic restriction of Lotagnostus to lower slope and basinal environments that prevented association with endemic shallow marine taxa, renders correlation into the biostratigraphy of Laurentian upper slope and platform imprecise on the order of 10s, if not 100s of meters.